Exploring the metabolic dynamics, storage stability, and functional potential of Lacticaseibacillus rhamnosus Probio-M9-fermented milk - Xiaoye Liu; Kaiyang Liu; Jie Yang; Hui Qiao; Lai-Yu Kwok; Wenyi Zhang (Journal of Dairy Science)
ABSTRACT: Lacticaseibacillus rhamnosus Probio-M9 (Probio-M9), a probiotic strain sourced from healthy breast milk, is recognized for its resilience to gastric and bile acids, along with its potential health benefits for infants. Its unique origin may influence its metabolic properties and effectiveness, and it has garnered increasing interest within the scientific community in recent years. However, research on its efficacy as a starter culture for milk fermentation and the associated metabolic shifts remains limited. This study aimed to track the dynamic metabolomic changes of Probio-M9 during the fermentation process. We used Probio-M9 as the sole inoculant for milk fermentation, collecting samples at 1.5- to 3-h intervals to monitor fermentation progression. Moreover, the metabolomics changes of the fermented milk were investigated after a 28-d storage period to evaluate post-storage stability. Metabolite profiles were generated using ultra-high performance liquid chromatography coupled with quadrupole time-of-flight MS with multiple segment extraction. A total of 34 representative differential metabolites were identified, primarily comprising peptides and saccharides, followed by acids, amino acids, alcohols, aldehydes, ketones, and intermediate metabolites. Notably, substantial alterations in metabolite levels were observed between 10.5 and 12 h into the fermentation process. Functional metabolites like syringaldehyde, leucic acid, and gentianose accumulated toward the end of fermentation, whereas peptides emerged as the main differential metabolites after the 28-d storage period. The study offers novel insights into the metabolic dynamics of Probio-M9 during fermentation and storage, which may inform the optimization of Probio-M9-fermented milk production processes. However, it is important to note that the focus of this study on a single starter strain may limit the generalizability of these findings.